Data-driven clustering of combined Functional Motor Disorders based on the Italian registry - Mostile, Giovanni; Geroin, Christian; Erro, Roberto; Luca, Antonina; Marcuzzo, Enrico; Barone, Paolo; Ceravolo, Roberto; Mazzucchi, Sonia; Pilotto, Andrea; Padovani, Alessandro; Romito, Luigi Michele; Eleopra, Roberto; et al. (Frontiers in Neurology, 2022)
Introduction. Functional Motor Disorders (FMDs) represent nosological entities with no clear phenotypic characterization, especially in patients with multiple (combined FMDs) motor manifestations. Data-driven approach using cluster analysis of clinical data has been proposed as analytic method to obtain non-hierarchical unbiased classifications. The aim of the study was to identify clinical subtypes of combined FMDs using a data-driven approach in order to overcome possible limits related to “a priori” classifications and clinical overlapping. Methods. Data were obtained by the Italian Registry of Functional Motor Disorders. Patients identified with multiple or “combined” FMDs by standardized clinical assessments were selected to be analyzed. Non-hierarchical cluster analysis was performed based on FMDs phenomenology. Multivariate analysis was then performed after adjustment for principal confounding variables. Results. From a study population of n=410 subjects with FMDs, we selected n=188 subjects [women: 133 (70.7%); age: 47.9±14.4 years; disease duration: 6.4±7.7 years] presenting combined FMDs to be analyzed. Based on motor phenotype, two independent clusters were identified: Cluster C1 (n=82;43.6%) and Cluster C2 (n=106; 56.4%). Cluster C1 was characterized by functional tremor plus parkinsonism as main clinical phenotype. Cluster C2 mainly included subjects with functional weakness. Cluster C1 included older subjects suffering from anxiety who were more treated with botulinum toxin and antiepileptics. Cluster C2 included younger subjects referring different associated symptoms such as pain, headache and visual disturbances, who were more treated with antidepressants. Conclusions. Using a data-driven approach of clinical data from the Italian registry we differentiated clinical subtypes among combined FMDs to be validated by prospective studies.